1991
DOI: 10.2307/2409887
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation of Polish Populations of Sorex araneus L. III. Interchromosomal Recombination in a Hybrid Zone

Abstract: Two parapatric chromosomal races of the common shrew (Sorex araneus) in Poland differ in their complement of metacentric arm combinations: hk, io, gr, nm (race IV), and hi, ko, gm, np (race II). In hybrids, these eight race-diagnostic metacentrics form two randomly segregating complexes. The first complex (C ) occurs in the form of a ring configuration ok/kh/hi/io, or a chain o/ok/kh/hi/i (when there is Robertsonian polymorphism of the element io). The second complex (C ) always takes the form of a six-element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 2 publications
2
62
0
Order By: Relevance
“…The Lepel race was first found in Belarus by Bulatova et al (2000) and the Kiev race first found in Ukraine by Mishta (1994). af, be, g/r, h/k, i,jl, m/n, o, p, q, tu This race is found locally in north-eastern Poland (Fedyk 1986, 1995, Fedyk and Lenieć 1987 and in the Kaliningrad region (Orlov et al 1996). We found this race in one population on the Baltic coast of western Latvia.…”
Section: Localitymentioning
confidence: 48%
See 1 more Smart Citation
“…The Lepel race was first found in Belarus by Bulatova et al (2000) and the Kiev race first found in Ukraine by Mishta (1994). af, be, g/r, h/k, i,jl, m/n, o, p, q, tu This race is found locally in north-eastern Poland (Fedyk 1986, 1995, Fedyk and Lenieć 1987 and in the Kaliningrad region (Orlov et al 1996). We found this race in one population on the Baltic coast of western Latvia.…”
Section: Localitymentioning
confidence: 48%
“…It is noticeable that most of the races possess metacentric hk. This metacentric is also found in the Łęgucki Młyn race (Wójcik 1986) and Gołdap race (Fedyk 1986(Fedyk , 1995 in Poland and in the Lemi race (Halkka et al 1987) in south-eastern Finland. So, our data allow the range of hk to be determined: it occurs along the coast of the Baltic Sea from north-eastern Poland to south-eastern Finland.…”
Section: Relationships With Other Chromosome Racesmentioning
confidence: 74%
“…Malczyce 51°14'N,16°30'E 6 20 hi,gm,ko,nr,p,q The description of the chromosome races of the common shrew in Poland was made according to the preliminary suggestions of the International Sorex araneus Cytogenetics Committee (Searle et al 1991). Data used for description of the races came from Wójcik and Fedyk (1985), Wójcik (1986), Fedyk (1987, Fedyk and Lenieć (1987), and the present study. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous karyotypic races have been described all over the extensive range of the common shrew (Halkka et al 1974, Fredga and Nawrin 1977, Krai et al 1981, Searle 1984, 1988a, b, Wójcik and Fedyk 1985, Zima and Krai 1985, Fedyk 1986, Hausser etal. 1986, Wójcik 1986, 1989, Fedyk and Lenieć 1987, Frecga 1987, Zima et al 1988, Aniskin and Lukianova 1989, Briinner 1991.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation